Pengaruh Current Ratio (CR), Return On Assets (ROA) dan Assets Growth (AG) terhadap Stuktur Modal (DER) pada PT Indofood Sukses Makmur Tbk periode 2014-2023 - Lestari, Siska; Supiyadi, Dedi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aimed to examine the effects of Current Ratio (CR), Return on Assets (ROA), and Assets Growth (AG) on the debt-to-equity ratio (DER) of PT Indofood Sukses Makmur Tbk from 2014 to 2023. The research employed descriptive and verification methods using a quantitative approach. Data was collected through documentation, utilizing secondary data from quarterly financial reports. The study used purposive sampling. Results of partial hypothesis testing (t-test) revealed that the Current Ratio (CR) had a significant positive effect on the debt-to-equity ratio (DER). In contrast, Return on Assets (ROA) and Assets Growth (AG) had positive but non-significant effects on DER. Simultaneous hypothesis testing (F-Test) showed that CR, ROA, and AG significantly impacted DER at PT Indofood Sukses Makmur Tbk, accounting for 50.9% of its variation. The remaining 49.1% was attributed to other factors not examined in this study